1974
DOI: 10.1115/1.3445854
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Film Cooling Following Normal Injection Through a Round Hole

Abstract: Heat transfer is measured downstream of perpendicular injection of an air jet through a single hole into a turbulent mainstream boundary layer. The heat transfer coefficient, calculated from wall temperature measurements with a constant heat flux from the test surface, is determined with injection of both heated and unheated jets. The heat transfer coefficient near the hole is as much as 45 percent larger than the value without injection for a blowing rate (mass flux ratio) of 2.0. Even far downstream, the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The film cooling technique is an effective approach to protect the advanced gas turbine airfoils [6][7][8]. In this process, cooling gas passes through the internal cooling channels and emerges from the film holes to create a blanket of thin film over the outer surface of the airfoil thus preventing the direct contact of the hot gases and the coverage surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The film cooling technique is an effective approach to protect the advanced gas turbine airfoils [6][7][8]. In this process, cooling gas passes through the internal cooling channels and emerges from the film holes to create a blanket of thin film over the outer surface of the airfoil thus preventing the direct contact of the hot gases and the coverage surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…To go over the details of each study is well beyond the allotted space in this manuscript. We, however, would like to refer the reader to the work of pioneers such as Goldstein et al [1], Eriksen and Goldstein [2], and Pedersen et al [3] in this field who investigated the effects of main parameters such as hole geometry, density ratio, and blowing ratio on three-dimensional film cooling. Bogard et al [4] and Sen et al [5] reported adiabatic film cooling effectiveness values and heat transfer coefficients downstream of compound angle holes.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of injection geometry and injection ratio have been experimentally investigated by a number of workers. Ramsey and Goldstein (1971), Eriksen and Goldstein (1971), Eriksen and Goldstein (1974), investigated the effect of M and ao on jet trajectory and spread. Kruse and Metzinger (1984) did a systematic study on the effect of M, a o and p/d on the spanwise averaged effectiveness (n).…”
Section: Introductionmentioning
confidence: 99%